Oral Delivery of Biologics via the Intestine - Roger New (MDPI AG, 2020)
Biologics are currently one of the most promising avenues for therapeutic interventions in conditions such as metabolic disease, ageing and inflammatory disorders, and for chronic ailments, oral delivery of such medicines has for years been recognised as an important goal. Despite decades of intensive research, oral delivery of biologics is only just starting to prove feasible. There has been much talk about the barriers to uptake of biologics, and indeed, one function of the intestine is to prevent, in one way or another, passage of unwanted materials across the gut, and yet, grams of biological agents both large and small pass across the intestinal cell wall every day. This review first describes the functioning of the gut under normal circumstances, then identifies the principle biological mechanisms which have been harnessed successfully, to date, to achieve oral uptake, outlining the pros and cons of each approach. Examples with different biologics are given, and information on result of the latest clinical trials is provided, where available.